Assessing the factors affecting draught beer hygiene and validation of a novel dispense system - Mallett, James Robert (2020)
In 2018, a significant 2.2 billion litres of beer were sold on draught throughout the U.K. representing 41.8% of all beer sold. Assuring the quality of draught beer at the point of dispense should be of paramount importance to both brewers and retailers alike, improving profits and protecting brand reputation. However, they face many challenges in doing so, due to; variable line cleaning efficacy, product rate of sale and dispense system complexity. This project set out to perform, for the first time, quantitative analysis of the U.K. beer on-trade marketplace with the primary focus on improving beer quality across the bar. Initially, the traditional beer forcing method was applied in a novel way, to measure beer quality directly at the point of dispense. Greater understanding of beer quality available to consumers was gained through a wide-ranging survey of beer quality in 65 on-trade accounts across the East Midlands was performed with extensive data analysis showing significant difference between beer styles, price doesn’t always mean better quality and a higher number of taps on the bar negatively impacted beer quality. Subsequently, a novel dispense system and four market leading line cleaning chemicals, were stringently tested for their hygienic performance using beer forcing, biofilm quantification and Headspace-Gas Chromatography to identify effective innovations in dispense line materials, cooling systems and cleaning methodology. Finally, the project took a first look at the total microbiome of a beer dispense system, identifying microorganisms present in; the keg, biofilm and dispensed beer. Microorganisms such as B. thurigiensis and R. mucilaginosa were identified alongside the much-reported beer spoilers; L. brevis, A. aceti and B. bruxellensis.